Iron and Steel - The Importance of Manganese in the Steel Industry (with Discussion) - H. M. Boylston (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
Metallic manganese was first produced in 1773, by Sven Rinmann, a Swedish mineralogist. In 1799, William Reynolds, of Ketley, England, obtained a patent on the use of manganese dioxide in the manufacture of steel, and in 1808 an English patent was granted to John Wilkinson covering the use of manganese ore, or manganiferous ore, as an addition to iron ore in the blast furnace for the production of a superior grade of pig iron. Karsten showed in 1816 that manganese increased the hardness of iron without decreasing its malleability or toughness, while it caused pig iron to be more white in fracture and more fusible. The first practical application of manganese to steel-making, however, is attributed to Josiah Heath who discovered in 1839 (less than 90 years ago) that manganese conferred upon steel the properties of being more easily worked and welded under the hammer. When Bessemer invented the pneumatic process of steel-making which now bears his name he was at first successful because, as it afterward developed, he was using a Swedish pig iron high in manganese. When his supply of this material ran out, he used a low-manganese pig from English sources and failed signally to produce a steel which could be rolled, while his Swedish licensees were continuing their successful application of his method. And it was not until Robert Mushet, in 1856, suggested the addition of manganese in the form of spiegeleisen to the molten product of the converter that success again came to Bessemer. In 1866, William Siemens patented the use of ferromanganese as an addition to molten steel to counteract the bad effects of sulfur. It was in 1888 that Robert Hadfield published at some length his account of the effect of manganese as an alloying element in steel and described the unique properties of the now famous Hadfield manganese steel containing about 12 to 14 per cent. manganese and 1.25 per cent. carbon. Function or Manganese in Steel-making Bessemer's failure at one period of his experimental work to make steel which could be forged successfully was due to the fact that the